Reflections of Teachers' Participation in the eTwinning platform on Their Professional and Personal Development in Jordan - Alananbeh, Njoud Yousuf (Journal of Educational and Psychological Sciences, 2023)
The study aimed to know The Reflections of Teachers' Participation in the eTwinning platform on Their Professional and Personal Development in Jordan. Case study design, as one of the qualitative research models, was used in the study. The participants of the research consist of 10 volunteer teachers, working in state schools in the 2021 -2022 academic year, were noticeably active on the eTwinning platform where they carried out a variety eTwinning projects. The data was collected with semi-structured interview forms prepared for teachers who volunteered to participate in the study, and the content analysis method was used in the data analysis. According to the survey, instructors used the eTwinning platform to collaborate, take online courses, create projects, and advance their professional development. In describing their eTwinning activities, teachers also utilized words like collaboration, sharing, technological advancement, and creativity.
Keywords: eTwinning; personal development; professional development